Ergometric and physiological characteristics of special physical fitness of athletes in sports with endurance - Andrii Diachenko; Yurii Shkrebtii; Ye Chenging (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to determine the individual parameters of the training work modes on the rowing ergometer for the development of specific components of the functional support of athletes in sports with the manifestation of endurance. Material and methods: the study involved 25 kayakers, members of the Shandong Province, Jiangxi (China) teams. The Dansprint rowing ergometer (Denmark) was used to measure the ergometric power in real time. Oxygen consumption (VO2), CO2 emission level (VCO2), pulmonary ventilation (VE) were determined for each respiratory cycle using an Oxycon (Jaeger) mobile gas analyzer. Results: indicators of ergometric power, recorded in accordance with the level of response of the cardiorespiratory system in the process of modelling the components of the functional support of the special kayaker's performance. On this basis the modes of training means, and also the program of their target use in system of special functional training of rowers are developed. Conclusions: the effectiveness of the program of special functional training of rowers is proved. The result is an increase in the ergometric power and response of the cardiorespiratory system when modelling the components of the functional support of the special performance of rowers - fast kinetics, steady state and fatigue compensation.